Perspectives on Water Quality Monitoring Approaches for Behavioral Change Research - Jordan, Phil; Cassidy, Rachel (Frontiers in Water, 2022)
This review considers enhanced approaches to river water quality monitoring in north-western Europe following a series of study visits (11 sites in 7 countries). Based on the evidence gathered, options were identified and evaluated for their suitability to deliver specific water quality monitoring objectives and with a focus on effecting behavioural change. Monitoring programmes were diverse, ranging from enhanced grab sampling and laboratory analysis to sub-hourly sampling of multiple parameters and nutrients in autonomous high-specification, bank-side or mobile laboratories. Only one programme out of all the cases evaluated could readily identify influences that had produced behavioural change among stakeholders. This was principally because the other programmes were focussed on top-down policy change or surveillance rather than specifically focused on influencing behaviour. Nevertheless, programme researchers were clear that stakeholder engagement potential was very high and that the sites acted as important focus points for discussion on water quality issues, and so part of a suite of tools that might ultimately change behaviour. This identifies a space where water quality monitoring solutions could be adapted for behavioural change research.